Effects of Whey Protein Combined with Amylopectin/Chromium on the Muscle Protein Synthesis and mTOR Phosphorylation in Exercised Rats - Şahin, Kazım; Orhan, Cemal; Ozdemir, Oguzhan; Tuzcu, Mehmet; Şahin, Nurhan; Ojalvo, Sara Perez; Komorowski, James R. (Springernature, 2024)
This study aimed to examine the impact of varying doses of whey protein (WP) and amylopectin/chromium complex (ACr) supplementation on muscle protein synthesis (MPS), amino acid and insulin levels, and the rapamycin (mTOR) signaling pathways in exercised rats. A total of 72 rats were randomly divided into nine groups: (1) Exercise (Ex), (2) Ex + WPI to (5) Ex + WPIV with various oral doses of whey protein (0.465, 1.55, 2.33, and 3.1 g/kg) and (6) Ex + WPI + ACr to (9) Ex + WPIV + ACr with various doses of whey protein combined with 0.155 g/kg ACr. On the day of single-dose administration, the products were given by oral gavage after exercise. To measure the protein fractional synthesis rate (FSR), a bolus dose of deuterium-labeled phenylalanine was given, and its effects were evaluated 1 h after supplementation. Rats that received 3.1 g/kg of whey protein (WP) combined with ACr exhibited the most significant increase in muscle protein synthesis (MPS) compared to the Ex group (115.7%, p < 0.0001). In comparison to rats that received the same dose of WP alone, those given the combination of WP and ACr at the same dosage showed a 14.3% increase in MPS (p < 0.0001). Furthermore, the WP (3.1 g/kg) + ACr group exhibited the highest elevation in serum insulin levels when compared to the Ex group (111.9%, p < 0.0001). Among the different groups, the WP (2.33 g/kg) + ACr group demonstrated the greatest increase in mTOR levels (224.2%, p < 0.0001). Additionally, the combination of WP (2.33 g/kg) and ACr resulted in a 169.8% increase in 4E-BP1 levels (p < 0.0001), while S6K1 levels rose by 141.2% in the WP (2.33 g/kg) + ACr group (p < 0.0001). Overall, supplementation with various doses of WP combined with ACr increased MPS and enhanced the mTOR signaling pathway compared to WP alone and the Ex group.
Keywords: Whey protein; Chromium; Amylopectin; mTOR; Muscle protein synthesis; Insulin